Resposta :
Vamos là.
a)
f(x) = 2x + 5
inversa
y = 2x + 5
trocando y por x e x por y
x = 2y + 5
2y = x - 5
y = (x - 5)/2
b)
f(x) = -3x + 1
inversa
y = -3x + 1
trocando y por x e x por y
x = -3y + 1
3y = 1 - x
y = (1 - x)/3
![Ver imagem ALBERTRIEBEN](https://pt-static.z-dn.net/files/d07/8a80ef1e7693c705151a5cb4c09be910.jpg)
Vamos là.
a)
f(x) = 2x + 5
inversa
y = 2x + 5
trocando y por x e x por y
x = 2y + 5
2y = x - 5
y = (x - 5)/2
b)
f(x) = -3x + 1
inversa
y = -3x + 1
trocando y por x e x por y
x = -3y + 1
3y = 1 - x
y = (1 - x)/3